PELATIHAN TARI DALAM PENGEMBANGAN DIRI DI SMA PEMBANGUNAN LABORATORIUM UNP PADANG - Miftahul Rizka; Indrayuda Indrayuda; Fuji Astuti (SENDRATASIK UNP, 2018)
Abstract This article aimed to describe Dance Training in Self Development Development at SMA Pembangunan of UNP Padang. This research was a qualitative research with descriptive type, the object of the research was SMA Pembangunan of UNP Padang. Data collection techniques used were literature study and observation. The data analysis used in this research was interpretation techniques. The results showed that the implementation of dance self-development at SMA Pembangunan of UNP Padang did not run smoothly, assessed from the slow implementation process of students in responding to the material given because of the lack of applying this method by the coach in the school. The demonstration method conducted by the trainer was not enough to provide training to students because to produce creative students who were active in dancing need special direction and training.Keywords: Dance Training, Self Improvement